2014
DOI: 10.1007/s00213-013-3417-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age at the onset of drinking to intoxication and chronic ethanol self-administration in male rhesus macaques

Abstract: Rationale Consumption of alcohol begins during late adolescence in a majority of humans, and the greatest drinking occurs at 18–25 years then decreases with age. Objectives The present study measured differences in ethanol intake in relation to age at the onset of ethanol access among non-human primates to control for self-selection in humans and isolate age effects on heavy drinking. Methods Male rhesus macaques were assigned first access to ethanol during late adolescence (n = 8), young adulthood (n = 8)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 40 publications
6
40
0
Order By: Relevance
“…All procedures were conducted in accordance with the NIH and the Guide for the Care and Use of Laboratory Animals and approved by the Oregon National Primate Research Center IACUC. Data analysis on ethanol self-administration and MRI structural brain imaging from these animals have been published (Helms et al 2014; Kroenke et al 2014). …”
Section: Methodsmentioning
confidence: 99%
“…All procedures were conducted in accordance with the NIH and the Guide for the Care and Use of Laboratory Animals and approved by the Oregon National Primate Research Center IACUC. Data analysis on ethanol self-administration and MRI structural brain imaging from these animals have been published (Helms et al 2014; Kroenke et al 2014). …”
Section: Methodsmentioning
confidence: 99%
“…Because ethanol intake did not appear to modulate sEPSC amplitude, our results suggest that age of onset of ethanol drinking is not likely a risk factor for the development of aberrant synaptic function in the BNST. Interestingly, we have previously shown that age of onset is a risk factor for heavy drinking in this translational model (Helms et al, 2014b), suggesting that alterations in excitatory synaptic transmission in the BNST are more likely related to the consequences, rather than the risk, of chronic ethanol consumption.…”
Section: Discussionmentioning
confidence: 78%
“…Body weights were recorded weekly throughout the study. Alcohol intake and blood alcohol concentration data for some of these subjects have been published elsewhere [37, 38]. …”
Section: Methodsmentioning
confidence: 99%